Kinematic and kinetic characteristics of treadmill roller skiing and validation of force measurement roller skis - Zhao, S. (University of Jyväskylä, 2023)
Effective skiing biomechanics has been identified as one of the most important elements that could enhance performance in cross-country skiing. This study aimed to describe the biomechanical characteristics in treadmill roller skiing by simultaneously measuring the 2D forces from skis, the force from poles, and the kinematic data. The force acting on skiers` COM in the forward direction is the forward propulsion, and several approaches can be used to calculate it. These approaches were compared to discover the most suitable one (Article I). We mainly concentrated on the V2 skating technique, in which both skis and poles are used for forward propulsion. The biomechanical characteristics of this technique were investigated at different inclines (Article II) and speeds. The contributions from the skis and poles were also investigated while changing the treadmill speed using the point of view of external power (Article III). Finally, a new force measurement roller ski was validated for future studies (Article IV). Fourteen experienced skiers familiar with treadmill roller skiing participated in this study. Custom-made force measurement bindings, pole force sensors, and an eight-camera Vicon system were used to collect the force data and the trajectories of reflective markers (Article I-III). A pair of newly designed 2D force measurement roller ski, AMTI 3D force plates, and Vicon system were used as well (Article IV). The approach of calculating the forward component of GRF was found to be appropriate for quantifying the forward propulsion on a skier`s COM (Article I). The cycle characteristics of the V2 skating technique were found to be affected by the treadmill incline (Article II) and the speed. From the propulsive force point of view, increasing both pole and ski force effectiveness was found to be needed at steeper grades, but the relative contribution of pole forces versus ski forces in overcoming the total resistance did not change with incline (Article II). While the treadmill speed was changed, the poles contributed more propulsive force and were more effective than skis in the skiing direction, and the contribution of legs slightly increased when the speed was increased. From the external power point of view, the relative contribution from the poles towards the total external power was smaller than when analyzed in the force domain (Article III) and was not affected by the increasing speed. Finally, the newly designed 2D force measurement roller ski was found to be valid for use in future research (Article IV).